2015
DOI: 10.1007/s00414-015-1203-5
|View full text |Cite
|
Sign up to set email alerts
|

Everything clean? Transfer of DNA traces between textiles in the washtub

Abstract: Forensic genetic analysis of items possibly handled by a suspect or a victim is frequently inquired by the law enforcement authorities, since DNA left on touched objects can often be linked to an individual. Due to technical improvement, even poor traces, which seemed to be unsuitable for DNA analysis a few years ago, may be amplified successfully today. Yet, DNA can be transferred to a crime scene artificially or unintentionally without any primary contact between the individual and the object found at the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Moisture in the sample or surface also improves transfer of DNA either from the body or an intermediate surface [48], as does introducing friction into the contact [48,65]. This is perhaps consistent with reports of transferred DNA being recoverable from clean clothing items colaundered with used sheets or stained fabrics, as moisture, friction and continuous exposure would all be expected [65,111].…”
Section: Substrate or Surface Interaction With Trace Dnasupporting
confidence: 72%
“…Moisture in the sample or surface also improves transfer of DNA either from the body or an intermediate surface [48], as does introducing friction into the contact [48,65]. This is perhaps consistent with reports of transferred DNA being recoverable from clean clothing items colaundered with used sheets or stained fabrics, as moisture, friction and continuous exposure would all be expected [65,111].…”
Section: Substrate or Surface Interaction With Trace Dnasupporting
confidence: 72%
“…Each load of laundry was washed with 70 mL laundry detergent, at 40°C for 70 min, which is the most frequently used washing program for delicate fabrics such as clothing. Similar washing conditions were used by others . The laundry was then air‐dried and packed with appropriate care (gloves, mask) to avoid contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it has been shown that sperm cells have been transferred from one item to another during laundry [7,20,21,22]. However, the possibility of shed epithelial cells transfer, sufficient for STR profiling, through laundry was shown to be unlikely [6]. In reality, a single laundry may contain many clothing articles from several individuals and contain various types of e.Proofing http://eproofing.springer.com/journals/printpage.php?token=ZGH0M... biological material.…”
Section: Dna Presence In Washing and Drying Machinesmentioning
confidence: 99%
“…The possibility of secondary transfer of biological material is a major concern in forensic DNA interpretation. With continuously increasing sensitivity of commercially available STR kits, better PCR performance of inhibited samples, along with numerous improvements in collection, extraction and amplification methods, minute amounts of DNA, down to just tens of picograms, are sufficient to obtain a comparable DNA profile (reviewed by van Oorschot et al) [6]. Increased sensitivity makes the probability of detecting a profile from secondary transfer DNA source more likely to occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation